Theoretical and experimental study of damaged reinforced concrete shear walls strengthened with FRP composites. (1st June 2023) - Toduţ, C.; Dan, D.; Stoian, V.; Fofiu, M.
Abstract: The present paper presents the results of a theoretical and experimental program developed to study the seismic performance of precast reinforced concrete wall panels, strengthened with composite materials. These type of elements, also known nowadays as lightly reinforced shear walls with medium ductility (DCM), were widely used between 1955 and 1990 in different European countries (Serbia, Bulgaria, Polonia, Romania etc) being designed at that time without using the principle of shear force associated to the bending resisting moment. The current results refer to the investigation made on five specimens, one "as-built" solid wall, two walls with initial opening and two walls with cut-out opening. Usually, the cut-out procedure is applied cutting the concrete and reinforcements in order to create a new opening or enlarging an existing one. This intervention is widely requested by owners of apartments when they reconfigure the architecture of flats, but this procedure could influence the seismic behaviour by weakening the initial performance of the wall, especially due to the reduction of stiffness. In order to investigate the specimens' seismic behaviour, in-plane reversed cyclic lateral loadings were applied together with axial vertical loads. The specimens were monitored through the experimental tests using strain gauges, pressure and displacement transducers. Based on the experimental investigations performed on the reference undamaged walls, the specimens were repaired, then after were strengthened with the aim to reestablish the initial capacity of the elements without an important influence to the stiffness. The strengthening strategy proposed had used externally bonded FRP composite reinforcement (EBR-CFRP) and near-surface mounted FRP composite reinforcement (NSM-CFRP). The strengthened elements were tested again to study the behaviour of elements and the effectiveness of the proposed solutions. A numerical analysis was performed in order to check on the accuracy of using simple numerical models to predict the behaviour of strengthened shear walls.